‘A sort of breviary’: Arthur Symons, J. K. Huysmans and British Decadence - Matthew Creasy (Cahiers Victoriens et Edouardiens)
Arthur Symons’s description of J. K. Huysmans’s À rebours as ‘the breviary of decadence’ is widely cited by critics. It has had a significant influence on our understanding of Huysmans and upon histories of the Decadent movement more generally. This article examines the complex and changing textual history of this phrase as it is found in Symons’s journalistic writings. Across various periodicals, I trace the literary and social concerns that underlie Symons’s response to Huysmans during the 1890s. In the process, I uncover a set of conflicting motives and forms that can be traced to the contradictions and complexities of Decadence as a movement and concept. Symons’s comparison of À rebours to the Catholic breviary is exemplary here: although he first formulated this during 1892, he did not arrive at the familiar form in which it has been so influential until 1908, at which point he had disavowed Decadence for Symbolism. Drawing on recent work by Vincent Sherry I argue that this textual crux has broader consequences for our understanding of the untimely nature of Decadence, especially as it was encountered by English-speaking British readers. I show how Symons’s response to Huysmans epitomises the elusive and difficult nature of Decadence within the form of his writings, as much as his critical pronouncements.